New species of Mutillid Mimicking Enoclerus Gahan (Coleoptera: Cleridae: Clerinae) from Mexico and Central America - Rifkind, Jacques (Zootaxa, 2017)
Six new species of Enoclerus are described: E. delusus n. sp. from Costa Rica and Panamá, E. incanus n. sp. from México, E. zip n. sp. from México and El Salvador, E. reductesignatus n. sp. from Panamá, and E. citrinifrons n. sp. and E. philogenes n. sp. from Costa Rica. The new species are hypothesized to participate in a Batesian mimicry complex with boldly marked diurnal mutillid wasps as their model. Enoclerus crabronarius var. deletus Wolcott is elevated to species rank as E. deletus Wolcott new status. The identity of E. crabronarius is discussed.